1999
DOI: 10.1021/ma9904363
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance Imaging of Degradation and Stabilization Processes:  Behavior of a Hindered Amine Stabilizer in UV-Exposed Poly(acrylonitrile−butadiene−styrene) Polymers

Abstract: Introduction. Polymeric materials exposed to heat, mechanical stress, and ionizing or UV irradiation undergo degradation in the presence of oxygen due to the formation of reactive intermediates such as free radicals R • , RO • , and ROO • and hydroperoxides ROOH. 1-10 The degradation process can be accelerated by chromophores, free radicals, and metallic residues from the polymerization reactions. The structural and morphological changes in the polymer properties due to exposure to environmental factors are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 20 publications
3
56
1
Order By: Relevance
“…Actually, by recording the spectrum at 330 K no significant differences in the line shape were observed with respect to the room temperature spectrum. This contrasts with what found by Schlick and coworkers [9,10] in the EPR spectra of irradiated ABS samples stabilized with Tinuvin 770. They reported the presence of two superimposed spectra assigned to a ''fast'' component located in domains essentially consisting of polybutadiene sequences (T g % 200 K) and a ''slow'' component located in domains consisting of polystyrene (T g % 370 K) or polyacrylonitrile sequences (T g % 360 K).…”
Section: Epr Spectracontrasting
confidence: 90%
See 1 more Smart Citation
“…Actually, by recording the spectrum at 330 K no significant differences in the line shape were observed with respect to the room temperature spectrum. This contrasts with what found by Schlick and coworkers [9,10] in the EPR spectra of irradiated ABS samples stabilized with Tinuvin 770. They reported the presence of two superimposed spectra assigned to a ''fast'' component located in domains essentially consisting of polybutadiene sequences (T g % 200 K) and a ''slow'' component located in domains consisting of polystyrene (T g % 370 K) or polyacrylonitrile sequences (T g % 360 K).…”
Section: Epr Spectracontrasting
confidence: 90%
“…Very recently thermal and UV oxidative degradation of ABS stabilized with Tinuvin 770, has been investigated by means of the EPRI technique by Schlick and co-workers. [9,10] Two spectral components were detected in the EPR spectra: a ''fast'' component located in domains dominated by polybutadiene sequences and a ''slow'' component located in domains dominated by polystyrene or polyacrylonitrile sequences. It was also found that the polybutadienerich domains in ABS are the more vulnerable to UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of oxygen diffusion in determining the spatial distribution of nitroxides inside irradiated polymers and its role in the degradation mechanism of the polymeric materials may possibly explain the results obtained in different polymeric matrices [21] and requires a deeper investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They originated from hindered amines used as stabilizers. Lucarini et al carried out detailed studies on PP using 1D EPRI [23][24][25], Marek et al extended the work to polystyrene [26], while Schlick and collaborators used both 1D EPRI and 2D SSI to study the degradation of heterophasic system such as poly(acrylonitrile-butadiene-styrene) and propylene-ethylene copolymers [27,28], or very recently to measure diffusion coefficients of nitroxide radicals in propylene-ethylene copolymers [29] (for review on this topic see Refs. [30][31][32] by Schlick).…”
Section: Introductionmentioning
confidence: 99%